Expression of the transcription factor encoding gene StTCP23 in potato plants infected with the tuber spindle viroid - N. V. Mironenko; A. S. Orina; N. M. Lashina; О. S. Afanasenko (Труды по прикладной ботанике, генетике и селекции)
Background The potato spindle tuber viroid (PSTVd) is the smallest of all known potato pathogens. PSTVd is a circular, single-stranded RNA molecule that does not code for proteins. Symptoms caused by PSTVd lead to a significant reduction in tuber yield or death of the plant. PSTVd infection triggers the silencing of host-plant genes and induces disease symptoms in the plant via vd-sRNA. The StTCP23 potato gene which encodes a transcription factor is one of the targets of PSTVd. The aim of the study was to assess the effect of inoculation of potato plants of cv. ‘Colomba’ with the PSTVd viroid NicTr-3 strain on the StTCP23 expression in infected plants.Materials and methods. Potato plants of cv. ‘Colomba’ were inoculated with leaf sap of the tomato cv. ‘Rutgers’ in which the PSTVd viroid NicTr-3 strain was propagated. RT-PCR with specific primers was used to confirm the infection of potato plants with the viroid. Diversity of RNA molecules in the PSTVd population was revealed using RT, cloning, and sequencing of the viroid. The expression of the StTCP23 gene in infected potato plants was assessed by quantitative PCR with the ef1α gene as a reference.Results. Symptoms of infecting ‘Colomba’ plants with the PSTVd viroid strain NicTr-3 were not detected, while the presence of the viroid in potato leaves was confirmed by molecular methods. Ten mutations were found in individual variants of the PSTVd strain NicTr-3, responsible for reducing the viroid’s aggressiveness. An increase in the expression of StTCP23 was shown at 3 time points in ‘Colomba’ plants inoculated with the NicTr-3 strain compared to the control.Conclusion. The mechanism of interaction between PSTVd and the StTCP23 gene in an infected potato plant is not universal and depends both on the potato genotype and viroid strain. Additional studies are required to prove the existence of specific interaction mechanisms between the host-plant and viroid strain genotypes.